2007
DOI: 10.1001/jama.298.16.1888
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and CD4 Cell Response in Children Receiving Antiretroviral Therapy at Primary Health Care Facilities in Zambia

Abstract: Y THE END OF 2006, AN ESTImated 2.3 million children worldwide were living with human immunodeficiency virus type 1 (HIV-1). 1 Although most children acquire the virus through largely preventable mother-to-child transmission, roll-out of perinatal HIV prevention services has been sluggish worldwide. As a result, each day more than 1000 children become newly infected. 2 Without treatment, approximately half will die by their second birthday 3 ; however, lives can be extended and morbidity avoided with combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

71
303
11
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 309 publications
(395 citation statements)
references
References 23 publications
71
303
11
10
Order By: Relevance
“…Considerable efforts to control the spread of HIV in the region have been made with an increasingly higher number of people receiving free combined antiretroviral therapy (cART) (Joint United Nations Programme on HIV/AIDS & World Health Organization 2009; World Health Organization, United Nations Children's Fund, UNAIDS 2009). As a result, mortality and morbidity rates among HIV-infected children have significantly reduced (Bolton-Moore, Mubiana-Mbewe, Cantrell, Chintu, Stringer, Chi, et al 2007;Ellis & Molyneux 2007;Janssen, Ndirangu, Newell & Bland 2010;Kiboneka, Wangisi, Nabiryo, Tembe, Kusemererwa, Olupot-Olupot, et al 2008;KIDS-ART-LINC Collaboration 2009;Nyandiko, Ayaya, Nabakwe, Tenge, Sidle, Yiannoutsos, et al 2006;Puthanakit, Aurpibul, Oberdorfer, Akarathum, Kanjananit, Wannarit, et al 2007;Wamalwa, Farquhar, Obimbo, Selig, Mbori-Ngacha, Richardson, et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable efforts to control the spread of HIV in the region have been made with an increasingly higher number of people receiving free combined antiretroviral therapy (cART) (Joint United Nations Programme on HIV/AIDS & World Health Organization 2009; World Health Organization, United Nations Children's Fund, UNAIDS 2009). As a result, mortality and morbidity rates among HIV-infected children have significantly reduced (Bolton-Moore, Mubiana-Mbewe, Cantrell, Chintu, Stringer, Chi, et al 2007;Ellis & Molyneux 2007;Janssen, Ndirangu, Newell & Bland 2010;Kiboneka, Wangisi, Nabiryo, Tembe, Kusemererwa, Olupot-Olupot, et al 2008;KIDS-ART-LINC Collaboration 2009;Nyandiko, Ayaya, Nabakwe, Tenge, Sidle, Yiannoutsos, et al 2006;Puthanakit, Aurpibul, Oberdorfer, Akarathum, Kanjananit, Wannarit, et al 2007;Wamalwa, Farquhar, Obimbo, Selig, Mbori-Ngacha, Richardson, et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have explored factors associated with LTFU in children (Bolton-Moore et al 2007;De Baets et al 2007;Ioannidis, Taha, Kumwenda, Broadhead, Mtimavalye, Miotti, et al 1999). However, few studies have examined this from the perspective of the caregivers responsible for taking these highly vulnerable children to care (Vreeman, Nyandiko, Ayaya, Walumbe, Marrero & Inui 2009;Yeap, Hamilton, Charalambous, Dwadwa, Churchyard, Geissler, et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In [11] As evidence mounts for successful initiation of paediatric ART care in rural and urban community-based PHC clinics, [13][14][15][16][17][18] the need to evaluate paediatric down-referral outcomes remains. A systematic review of decentralised HIV care (including three studies with paediatric data) demonstrated comparable outcomes, with similar or reduced patient attrition and death at 12 months.…”
mentioning
confidence: 99%
“…The clinical care provided at these sites is standardized and has been described elsewhere. 5,10 Implementation was staggered for logistical reasons and the order of selected clinics was based on geographic location, existing clinical infrastructure, and size of catchment population. Expansion was likewise strategic to meet Zambian Ministry of Health priorities for equitable and rapid expansion.…”
Section: Settingmentioning
confidence: 99%
“…5,10 In an effort to measure the impact of ART service expansion at the community level, we conducted a series of cross-sectional household surveys across Lusaka, which were timed according to program implementation. This project was designed to evaluate whether clinic-level services for HIV care and treatment would positively impact the surrounding communities through reduced population-level mortality, improved knowledge and attitudes towards HIV, and improved knowledge and attitudes related to antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%